BRANDING FROM SMALL BUSINESS AND VIDEO CONTENT CREATION IN GEN Z DOMINATED ERA - Mukadis, Panji Nandiasa Ananda (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The Business Management program at Swiss German University, in collaboration with Markas Bandung, organized a Corporate Social Responsibility (CSR) workshop titled